Eurasian Association of Cardiology (EAC)/ National Society of Heart Failure And Myocardial Disease (NSHFMD) guidelines for the diagnosis and treatment of chronic heart failure (2024) - S. N. Tereshchenko; I. V. Zhirov; T. M. Uskach; M. A. Saidova; S. P. Golicyn; E. M. Rimskaya; S. N. Nasonova; O. Yu. Narusov; A. A. Safiullina; A. S. Tereshchenko; O. V. Stukalova (Евразийский Кардиологический Журнал, 2024)
The purpose of this guide is to assist cardiologists in the management of patients with chronic heart failure (CHF) in accordance with the available modern evidence base. This manual contains data on the diagnosis, treatment, and rehabilitation of patients with chronic heart failure and data on acute decompensation of heart failure.